THE EPIPHANY OF FACES OF COVID-19 PANDEMIC AS REFLECTED IN EDGAR ALLAN POE’S THE MASQUE OF THE RED DEATH - Anicleta Yuliastuti; Rommel Utungga Pasopati (UC Journal: ELT, Linguistics and Literature Journal, 2021)
Edgar Allan Poe’s The Masque of The Red Death is a famous story of a plague in which the infected ones died with blood coming out from pores. Prince Prospero as ruler of that area ignores it but then was killed by a figure with a face full of blood covered in a mask. In the COVID-19 pandemic, the infected ones are quite seen as terror and disgust. People stay away from them as if they are dirty and sinful. It is similar to how Red Masque and Red Death are indicated in Poe’s story. However, Emmanuel Levinas argues that the epiphany of the face invites people to be ethical to others. Then, how is the epiphany of the face reflected in Edgar Allan Poe’s The Masque of The Red Death? By using the qualitative method, written data, concepts, and theories are asserted to answer that question. Comparing Levinas’ explanation, Poe’s story, and today’s pandemic situation could bring in better insight into how the infected ones should be treated better. They must not be excluded, but they need our ethical compassion in answering their presence to us.